Probable transfusion transmission of West Nile virus from an apheresis platelet that screened non‐reactive by individual donor‐nucleic acid testing. Issue 2 (21st October 2019) - Hayes, Chelsea; Stephens, Laura; Fridey, Joy L.; Snyder, Robert E.; Groves, Jamel A.; Stramer, Susan L.; Klapper, Ellen
Abstract: BACKGROUND: Despite West Nile virus (WNV) blood donation screening using nucleic acid testing (NAT), donors with low viral loads not detected by mini‐pool‐NAT have led to transfusion transmitted (TT)‐WNV infection. We describe a probable case of fatal TT‐WNV infection from an individual donor (ID)‐NAT non‐reactive apheresis platelet donation. STUDY DESIGN AND METHODS: An apheresis platelet donation was WNV ID‐NAT reactive and prior donations from the same donor were investigated. A WNV ID‐NAT non‐reactive apheresis platelet unit collected 26 days earlier was transfused during heart transplantation to a patient who subsequently developed WNV neuroinvasive disease and expired. The source of the recipient's WNV infection was investigated. RESULTS: Twenty‐six days after collection of the suspect platelet unit, a donation from the same donor was WNV ID‐NAT reactive and WNV IgM and IgG positive. In addition to the suspect platelet unit, the heart transplant recipient who developed WNV infection received 17 blood components from 24 donors. Serologic testing performed on 11 of the remaining 24 donors (46%) was WNV IgM negative. Pre‐transplant recipient and heart donor samples tested WNV RNA and IgM negative. CONCLUSION: A probable case of fatal neuroinvasive TT‐WNV was linked to an infectious apheresis platelet unit undetected by WNV ID‐NAT. It is hypothesized that the suspect unit was collected early in the viremic period when viral RNA was below the limit‐of‐detection of the ID‐NAT assay. Implementation of ID‐NAT screening of blood donors has not entirely eliminated the risk of TT‐WNV infections, which may best be addressed by pathogen inactivation technologies.